Experimental and numerical studies on heat transfer characteristics of vertical deep-buried U-bend pipe to supply heat in buildings with geothermal energy. (1st January 2018) - Li, Chao; Guan, Yanling; Wang, Xing; Li, Gaopeng; Zhou, Cong; Xun, Yingjiu
Abstract: In this study, in-situ experiments and numerical simulations were used to study the heat transfer characteristics of a heat exchange system, a vertical deep-buried U-bend pipe with a buried depth of >2000 m to supply heat to buildings in Xi'an using geothermal energy. The in-situ experimental conditions include a constant inlet temperature and water flow rate in the deep-buried pipe, and the inlet and outlet water temperatures of the buried pipe were measured to obtain the dynamic heat transfer load of the buried pipe under the experimental conditions. Based on the experimental results, a full-scale numerical calculation model combining the heat transfer processes inside and outside the pipe was established and validated. Based on the model, the effects of water flow rate and running time of the system on the heat transfer capacity of the buried pipe were calculated and analyzed under the practical conditions of nonuniformity from the top to the bottom by considering the ground temperature and structure of rock and soil. The thermal effect radius and linear meter heat transfer of the buried pipe were also analyzed. Highlights: Buried depth of a deep-buried U-bend pipe heat exchanger was more than 2000 m. Heat transfer performance of the pipe was evaluated by in-situ experiments. A full-scale numerical model was established and experimentally validated. Heat transfer performance of a deep-buried pipe was studied for the first time.